Seasonal variability of sea surface height in the coastal waters and deep basins of the Nordic Seas. Issue 1 (12th January 2015) - Bulczak, Anna I.; Bacon, Sheldon; Naveira Garabato, Alberto C.; Ridout, Andrew; Sonnewald, Maike J. P.; Laxon, Seymour W.
Abstract Sea surface height measured by the Envisat radar altimeter over open ocean and from leads in sea ice are combined to generate a complete view of variability in the Nordic Seas, geographically and seasonally. The observed seasonal variability is decomposed using empirical orthogonal functions and is consistent with seasonal variations in steric and dynamic forcing. Wintertime increase in sea surface height on the east Greenland shelf is hypothesized to be caused by wind‐forced downwelling, which provides direct evidence for the regional play of coastal dynamics. High levels of eddy kinetic energy around the sea ice edge in Fram Strait and off east Greenland and Svalbard are consistent with the interaction of the wind with the ice edge.